Rural communities and ethnic identities in Latin America - Lifschitz, Javier Alejandro (2015)
This article has as its focus the new configurations of rural communities in Latin America. From the concept of neocommunities, we intend to show that traditional communities have been, since the last decades of the twentieth century, a privileged domain of public policies and social and cultural projects developed by NGOs, cultural tourism agents, Universities, the media and others. We observe that in maroon neocommunities in Brazil these modern agents develop actions of reconstruction, of practices and knowledges of the afrobrazilian universe which influence the dynamic of rural space.